Offshoring to a Developing Nation with a Dual Labor Market - Subhayu Bandyopadhyay; Arnab K. Basu; Nancy H. Chau; Devashish Mitra (Institute of Labor Economics (IZA), 2020)
We present a model of offshoring of tasks to a developing nation, which is characterized by a minimum wage formal sector and a flexible wage informal sector. Some offshored tasks are outsourced by the formal sector to the lower wage informal sector. An improvement in the productivity in performing offshored tasks in the developing country raises offshoring, but not necessarily formal-to-informal outsourcing, and, in response, the developed nation wage can fall. Productivity improvements in the informal sector expand both offshoring and outsourcing, and the developed nation wage must rise. When the minimum wage is reduced, the developed nation wage falls when most of the efficiency gains accrue to the informal sector.
Keywords: F1; F2; J4; J8; 330; offshoring; outsourcing; informal sector; dual labor markets